2017
DOI: 10.1158/2326-6066.cir-16-0182
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Methylation Modulates Indoleamine 2,3-Dioxygenase 1 Induction by Activated T Cells in Human Breast Cancers

Abstract: Triple-negative breast cancer (TNBC) cells are modulated in reaction to tumor-infiltrating lymphocytes. However, their specific responses to this immune pressure are unknown. In order to address this question, we first used mRNA sequencing to compare the immunophenotype of the TNBC cell line MDA-MB-231 and the luminal breast cancer cell line MCF7 after both were cocultured with activated human T cells. Despite similarities in the cytokine-induced immune signatures of the two cell lines, MDA-MD-231 cells were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…An immunomodulatory role for the enzyme indoleamine 2,3-dioxygenase (IDO), which catalyzes the conversion of tryptophan into kynurenine, has been suggested to have a role in macrophage functions 10 . Increased IDO activity is often associated with tumors and infectious diseases 11 . Several studies have described IDO-dependent T-cell suppression by antigen-presenting cells under many infectious and inflammatory conditions, indicating that biochemical changes due to tryptophan catabolism have a profound effect on T-cell proliferation and effector functions in tissue microenvironments 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…An immunomodulatory role for the enzyme indoleamine 2,3-dioxygenase (IDO), which catalyzes the conversion of tryptophan into kynurenine, has been suggested to have a role in macrophage functions 10 . Increased IDO activity is often associated with tumors and infectious diseases 11 . Several studies have described IDO-dependent T-cell suppression by antigen-presenting cells under many infectious and inflammatory conditions, indicating that biochemical changes due to tryptophan catabolism have a profound effect on T-cell proliferation and effector functions in tissue microenvironments 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, T‐IDO1 staining was not proportional to infiltrating CD8+ T cells some of the cases in our study, perhaps due to IDO1 also being constitutively expressed by tumor cells through poorly characterized oncogenic signaling pathways. Previous studies have revealed that intrinsic cellular changes triggered by poorly characterized genetic mutations and epigenetic modifications can also regulate T‐IDO1 expression; for example, either demethylated promoters or low expression of Bin1 could lead to highly inducible IDO1 expression in breast cancer . Both intrinsic and extrinsic mechanisms could be independently or jointly determining the T‐IDO1 level in the HCC microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanisms that regulate IDO1 expression are not completely understood, including in esophageal cancer. Recently, it has been reported that IDO1 expression was regulated by promoter methylation in breast cancer . Promoter methylation is associated with gene expression levels and changes in transcriptional function or malignant behavior of cancer cells.…”
Section: Introductionmentioning
confidence: 99%